Correlation Between Age And Pregnancy Duration Toward The Incidence Of Post Partum Bleeding At dr. H. Moch. Ansari Saleh Hospital Banjarmasin year 2015 - Sarkiah sarkiah; Agus Muliyawan; Trisnayusmianti Trisnayusmianti (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background : Postpartum bleeding is an important issue in obstetrics related to high maternal mortality. It is about 42% in Indonesia, 29% in South Kalimantan, 43,08% in Banjarmasin in 2012, and 2.40% at Dr. H. Moch. Ansari Saleh Hospital Banjarmasin in 2015.Purpose: Relationship Age and spacing of pregnancy with Bleeding Post in the Dr. h. Moch. Ansari Saleh Banjarmasin Hospital.Method : Analytic survey Research to entire population of mothers who experience postpartum bleeding at the Dr. H. Moch. Ansari Saleh Hospital Banjarmasin in 2015. It used secondary data from the register book during the year 2015, along with 77 people as a sample.Result: Research based on the analysis of the test data with the Chi-Square obtained results for age, the value of p = 0.181 mean values of α p (α = 0.5) then there was no meaningful correlation between age and the incidence postpartum bleeding. The value of pregnancy duration was p = 0.578, it means a value α p (α = 0.5) then there was no meaningful correlation between pregnancy duration and postpartum bleeding.Congclution: The incidence of postpartum bleeding was happened  most to 20-35 year old category (72.7%), pregnancy 2-4 years duration (64.9%), the primary hemorrhage (75.3%) and caused by retensio placenta (51.9%).Suggestion: Researcher provides for more samples and chooses other variables to be testedKeywords: Age, Pregnancy Duration, Postpartum Bleeding